Long-Distance Parenting and Family Resilience Strategies of Indonesian Migrant Workers in Taiwan - Iqbal, Muhammad; Gusman, Yuherina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
This study examines the resilience of Indonesian Migrant Worker (PMI) families in Taiwan and the strategies they apply in long-distance parenting. Using Henry’s family resilience model, it analyzes family risks, vulnerabilities, protection, adaptation, and socio-ecological factors. Data were collected through interviews with 25 PMIs in Taiwan, 25 left-behind children and 25 caregivers in Indonesia. The findings show that migration-related family risks are rooted in structural poverty, gendered labor regimes, and marital disruption, while vulnerability is shaped by low educational attainment, weak communication, and limited caregiving capacity. Religion emerges as a crucial protective resource in transnational family life. Beyond emotional coping, religious values provide moral guidance, sustain parental authority, shape caregiving practices, and support meaning-making across distance through practices such as religious instruction, pesantren-based (Islamic Boarding) care, and faith-informed role modeling. Family adaptation depends not only on individual agency but also on socio-ecological support, including faith-based organizations and migrant networks. The study extends family resilience theory by demonstrating how religion strengthens resilience processes in transnational families and highlights the importance of culturally grounded interventions for migrant family welfare.